Synthesis, structure and photoluminescence properties of Ho3+ doped TTB-BaTa2O6 phosphors - (:unkn) unknown (ELSEVIER, 2014)
Ho3+ doped TTB-BaTa2O6 phosphors were produced by the solid state reaction method. XRD analysis confirmed the formation of BaTa2O6 single phase which was accomplished by heat treatment at 1425 degrees C for 20 h. The crystal structure of TTB-BaTa2O6 allowed doping concentration of Ho3+ ions up to 10 mol%, maintaining a single phase composition. A second phase of HoTaO4 begins to appear at 15 mol%. The lattice structure and the crystallite sizes changed with the concentration of Ho3+. In SEM analysis, it was also shown that BaTa2O6 grain sizes changed with the concentration of Ho3+. EDS analysis revealed that the Ta/Ba ratio increased on the grains depending on Ho3+ concentration. Charge balance of the structure was formulated through the EDS results. In fluorometer analysis, a strong green emission (lambda(em) = 546.9 nm) was observed in the visible spectral region. The emission increased with the doping concentration of up to 2.5 mol%, and above this level decreased due to concentration quenching. (C) 2014 Elsevier Masson SAS. All rights reserved.
Keywords: BaTa2O6; TTB; Ho3+; Phosphors; Photoluminescence; RED EMITTING PHOSPHOR; ENERGY-TRANSFER; LUMINESCENCE PROPERTIES; CRYSTAL-CHEMISTRY; PHOTON AVALANCHE; BATA2O6; PHASE; CE3+; RAY; TA